Cerebral venous thrombosis and depression: a scoping review - Feras M. Almarshad; Dushad Ram (Medičnì Perspektivi, 2024)
Cerebral venous thrombosis is a rare condition involving thrombus formation in the venous sinuses of the brain, leading to impaired venous drainage, increased intracranial pressure, and brain damage. Depression frequently accompanies cerebral venous thrombosis patients with varying prevalence and characteristics across studies. This scoping review aims to synthesize current evidence on the prevalence and characteristics of depression among cerebral venous thrombosis patients, identify patterns of sinus involvement, and assess the impact on clinical and psychiatric outcomes. This study searched PubMed/MEDLINE, Embase, Scopus, Web of Science, and Google Scholar databases for case reports, retrospective studies, and clinical trials published within the last 20 years in articles related to depression and cerebral vein thrombosis. This review covered demographics, clinical characteristics, structural involvement, and outcomes. The prevalence of depression in patients with cerebral venous thrombosis ranged from 13% to 58.4%, influenced by factors such as pattern of  venous sinus involvement, other body systemic involvement, and individual characteristics. Patients were predominantly younger to middle-aged adults, with a significant female predominance. Common comorbidities were anemia, hyperhomocysteinemia, migraines, and hypertension. Most patients had favorable outcomes; however, persistent residual symptoms and variable clinical presentations were also noted, affecting long-term quality of life. The review highlights the need for standardized assessments and a multidisciplinary approach to cerebral venous thrombosis management, addressing both neurological and psychiatric aspects. Further research with larger, standardized studies is necessary to better understand the relationship between cerebral venous thrombosis and depression and to improve patient outcomes.